Rare clinical cases of tularemia - L. V. Rubis; O. V. Ekimova (Журнал инфектологии)
The most common clinical form of tularemia in Europe is ulcerative bubonic, which has a summer-autumn seasonality. When infected with water and food, the development of oropharyngeal and abdominal forms is possible. The rarity of registration of such forms is associated not only with the low frequency of such cases of infection, but also with the complexity of diagnosing diseases with an atypical clinic. Important for the correct diagnosis are the results of specific laboratory diagnostics and a qualitatively collected epidemiological history. The results of zooparasitological monitoring allow assessing the risk of infection in certain territories. The article provides descriptions of two cases of severe abdominal tularemia, registered in autumn 2021 – winter 2022 in the Republic of Karelia, which has been one of the most disadvantaged regions of Russia in recent years. In the first case, in a 15-year-old boy, the disease began acutely, the main symptoms were high fever, abdominal pain, vomiting, loose stools, foci of skin hyperemia with clear uneven edges without infiltration in the left knee joint and right inguinal region, hepatomegaly, mesoadenitis. In indirect gemagglutination reaction with tularemia diagnosticum on the third day from the onset of the disease antibodies in titer 1:640. Infection probably occurred when eating food during a trip to the forest zone of the city, where infected rodents were previously detected. In the second case, a 17-year-old girl living in a village was diagnosed with a peritonsillar abscess 3 weeks before a sharp rise in temperature, abdominal pain, vomiting and loose stools. Later he developed renal and hepatic insufficiency, polyserositis. The antibodies titer was 1:320 after 3 weeks and 1:2650 after 5 weeks. Infection probably occurred through consumption of rodent-contaminated vegetables.